Designing Renewable Energy Systems within Planetary Boundaries: A Textbook for Energy Engineers (Green Energy and Technology, 2025)
This open access book explores interdisciplinary sustainability for energy engineering students. Future generations of engineers need to be game changers. The book is designed to help future engineers redesign the world, avoid harmful lockdowns, and prevent the creation of new problems while transforming energy systems in economically profitable and ecologically sustainable ways. It explains the principles of planetary boundaries, addressing the most relevant ones throughout. The book's focus is on the primary methods for producing renewable power and heating. It discusses the fundamental technical and economic design principles involved. The book also covers key energy storage solutions and includes an overview of the impacts of renewable energy production on ecosystems. The book also serves as a useful guide for engineers working on renewable energy projects.